The Impact of Negative Workplace Gossip on Employees’ Organizational Self-Esteem in a Differential Atmosphere - Song, Xiaolei; Guo, Siliang (Frontiers in Psychology, 2022)
The level of employees’ organizational self-esteem does not only correlate with individual performance but has also become a key factor in determining the completion of team core tasks. Based on the theory of self-consistency, this study explores the correlation between negative workplace gossip and employees’ organizational self-esteem by revealing the intermediary role of workplace exclusion and poor-order atmosphere. A survey of 228 employees from enterprises in Shandong and Shanghai showed that negative workplace gossip exerted a significant negative impact on employees’ organizational self-esteem, suggesting that negative workplace gossip reduces employees’ organizational self-esteem in the context of Chinese organizations. In addition, workplace exclusion exerted a complete intermediary effect between negative workplace gossip and employees’ organizational self-esteem, and poor-order atmosphere perception played a partial intermediary role. This study uncovers the black box that negative workplace gossip affects employees’ organizational self-esteem and has a strong enlightening significance for management practice.